THE IMPORTANCE OF THE SCIENTIFIC HERITAGE OF "STATESHOKH SAMARKAND" IN THE EDUCATIONAL PROCESS - Shamsiyeva Maxbuba Sattorovna. (Western European Studies, 2024)
This article explores the profound impact of the scientific contributions of the state-owned Samarkand on the educational landscape. Through extensive analysis of literature, he studies the methodologies used in the introduction of Samaritan heritage into modern education. The results highlight invaluable insights from his work and their impact on educational practice. The discussion ends with proposals to maximize the educational benefits of Samarkand's scientific heritage, emphasizing the relevance of integrating its teachings into modern pedagogy.
Keywords: state-owned Samarkand; scientific heritage; education